THE RESPONSE OF PGF2 ? EXTRACTION RESULT OF BALI CATTLE SEMINAL VESICLE FLUID ON PROGESTERONE LEVEL OF LUTEAL PHASE IN THE MARE - Oka Pemayun, Tjok Gde; Mahaputra, Laba; -, Ismudiono; -, Soetjipto (Jurnal Veteriner, 2008)
The study was carried out to determine the response of PGF2 ? result extraction of Bali cattle seminal vesicle fluid on the level of progesterone. The seminal vesicle fluid was aspirated and then were. extracted with methanol. This reseach was conducted by devided the mare in the luteal phase into two groups. The first group were treated with PGF2 ? result extraction of Bali cattle seminal vesicle fluid and the second group were treated with dinoprost as a patent product of PGF2 ? were administered intra uterine. The level of progesterone was measured before (0 hours) treatment and at 24, 48, 72 hours after treatment. The level of Progesterone were determined by radioimmunoassay (RIA) technique. The result showed that PGF2 ? result extraction of Bali cattle seminal vesicle liquid decreased the progesterone level 73.03% at 24 hours and 92.79% at 48 Hours. However, there was no significant different between PGF2 ? result extraction of Bali cattle seminal vesicle liquid with PGF2 ? of paten product on the progesterone level decreased. In conclusion, PGF2 ? extraction of Bali cattle seminal vesicle liquid can decreas the level of progesterone in the mare with luteal phase.
Keywords: Seminal vesicle, PGF2 ?, progesterone, luteal phase